Penerapan Dimensi Profil Pelajar Pancasila Melalui Ekstrakurikuler PMR Sebagai Upaya Mewujudkan Karakter Peduli Sosial - Ramadhani Ayundi; Budiaman Budiaman; Martini Martini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research will discuss the application of the Pancasila student profile character in the Youth Red Cross extracurricular activities at SMP Negeri 1 Klapanunggal. The Pancasila student profile has six dimensions, namely faith, devotion to God Almighty, and noble character, global diversity, mutual cooperation, independence, critical reasoning and creative thinking. The Youth Red Cross is a form of extracurricular activity related to the humanitarian field which in its various activities can create the character of the Pancasila student profile. The method used in this research is descriptive method. The data collection techniques used include interviews, distributing questionnaires, observation, literature study and documentation. The data analysis technique involves describing the results of questionnaires and interviews until they are processed into conclusions. The results of this research show that the six dimensions of the Pancasila student profile can create positive characters for PMR extracurricular members. The most superior dimension in youth Red Cross extracurricular activities is mutual cooperation, where youth Red Cross extracurricular activities really reflect collaboration and social care in the form of programs, such as routine training every Saturday, daily UKS pickets, collaborating with outside parties, and picketing during ceremonies. Even though the mutual cooperation dimension is the most superior, the other dimensions are also closely interrelated to create the character of extracurricular members of the Red Cross in accordance with the Pancasila student profile and the guidelines of the Red Cross, namely the Tri Bakti and the Seven Red Cross principles.